Concomitant Total Wrist and Total Elbow Arthroplasty in a Rheumatoid Patient - Kane, Patrick M.; Stull, Justin D.; Culp, Randall W. (Journal of Wrist Surgery, 2016)
Background Concomitant arthroplasty has been described to have several benefits over multistage procedures. Ipsilateral total elbow and total shoulder arthroplasty has been reported with good outcomes in upper extremity concomitant arthroplasty. Case Description A 65-year-old woman presented with ipsilateral left-sided wrist and elbow joint degeneration as a result of longstanding rheumatoid arthritis. Concomitant total wrist and total elbow arthroplasty was performed with satisfactory results at both joints. She tolerated the procedure well and had an uneventful clinical course postoperatively. Literature Review Currently, no literature exists that describes one-stage total wrist and total elbow arthroplasty. Individually, total wrist and total elbow arthroplasty have both been reported to result in good outcomes and patient satisfaction. Previous studies have reported the utility of concomitant ipsilateral upper extremity procedures with a one-stage total elbow and total shoulder arthroplasty having been identified as a cost-saving procedure with expedited return to functionality versus a two-stage procedure. Clinical Relevance Patients with ipsilateral degenerative changes in the wrist and elbow should be considered on an individual case basis for concomitant total wrist and total elbow arthroplasty.
Keywords: rheumatoid; one-stage; concomitant; arthroplasty